Estudio exploratorio en gestión de proyectos - Saenz Arteaga, Arturo Rodolfo (2019)
Several authors argue that project management is conducted with quantitative techniques that correspond to a linear cause-effect behavior; however, it should be treated with techniques that correspond to a nonlinear cause and effect behavior. This study explores the behavior of project management under a non-linear cause-effect approach using chaos theory and four project management variables: time, human resources, quality, and cost. Parkinson's law and chaos theory are used; mathematical equations are formulated to explain nonlinear cause-effect behavior in project management. The study was conducted considering the experience of management in mining projects. The mathematical model found can be used by academics to deepen the analysis of the reasons for the complexity of project management. Also, this study is useful for managers in making decisions to calculate the expected duration of the project.